ZEN BUDDHIST PHILOSOPHY : BACKGROUND AND THE ESSENCE AND CONTEMPORARY LIFE - Boontawong, ฺBoonyawat; Bhavanabodhikun, Phrakhru (Journal of Graduate MCU KhonKaen Campus, 2021)
This article aims to (1) Studying the history of Zen Buddhism, (2) Analysis of Buddhist substance of Zen philosophy, and (3) Synthesis of Buddhist essence, Zen philosophy and contemporary life. "Zen" means meditation or contemplation is the use of the mind to focus on understanding the truth, and used as the name of a sect that is separate from Mahayana Buddhism, Separated from the sect "Theravada" After the 2nd Amendment. Mahayana Buddhism is a progressive group, not attached to the original form, Dare to think and interpret original teachings, especially when thinking and narrating, not only thinking and narrating, but also to bring them into practice in daily life. That is why Zen Buddhism spread widely, there is a growing number of worshipers respectively. The essence of Zen Buddhism is the view of "Buddhism" by Zen Buddhist Philosophy believes that all human beings can reach the Buddha image. And the view of "genuine mind" is pure mind. But later lust Prejudice makes human beings attached and fascinated. If humans destroy ignorance is a misunderstanding and enchantment. The mind will become the original mind. Today, there is a wide study of Zen Buddhism. By means of being conscious and conscious and awake in the present Relieve anxiety there is clearly happiness in life.